KETERBUKAAN DAN AKUNTABILITAS PEJABAT PUBLIK (Kerangka Pemikiran dan Analisa Kasus Kepegawaian Kota Batu) - Himawan Estu Bagijo (Perspektif, 2007)
Public servant have an abligation to transparent on public policy related to citizen interest. This value is one of the important point in the Democratic Government and Good Governance principles. To apply the principle of transparent and public accountability if is need General principle law of administration (government). The "Batu" case is "maladministration of public servant". The problem is the period and requirement of the promotion is contradictive with regulation. But for all of the problem the Mayor of Kota Batu and Chief of Regional Administration of Public Servant Regional II East Java should be responsible.